Religious Ambience on Social Media: A Case Study in A Pandemic Situation - Paranjoy Bordoloi (Al-Albab, 2020)
Social media has been crucially important today in the pandemic situation. This work is rooted in key questions: whether social media consumption increases during a pandemic and does the communicative action of social media target religious ambience? The findings show that the flow of messages has increased on social media platforms during pandemic. However, the communicative action of social media is not targeted toward religious ambience. This work is based on data collected through a qualitative survey in the context of Assam, a state of India. The study concludes the communicative action of social media depends on its users' profiles. Users’ profile is perhaps the determining factor regarding religious ambience on social media.